PENERAPAN STRATEGI BENAR ATAU SALAH DISERTAI KUIS UNTUK MENINGKATKAN PEMAHAMAN KONSEP DALAM PEMBELAJARAN MATEMATIKA SISWA KELAS VIII KABUPATEN PASAMAN BARAT - Verawati, Widya; Rismen, Sefna (Pendidikan Matematika, 2013)
The introduction of this research is caused by the lack studentâs understanding of mathematical concept. This research aim to: 1) to see growth studentâs understanding in mathematical concept eightth the grade of SMPN 1 Koto Balingka used true or false strategy with quiz. 2) To know the studentâs understanding of mathematical concept used true or false strategy with quiz is better than use conventional strategy. The design this is experimental research. Population in this research is eightth grade studentâs SMPN 1 Koto Balingka academic year 2012/2013. The technique sampling of this is research random, instrument in this research is: 1) quiz as functioning to measure studentâs understanding in mathematical concept. 2) final test which in form of essay. Technique analysisÂ  data use test of with one side. The result of this research is obtained by ttest=7,30 and ttable= 1,63 because ttest>ttable so hypothesis is accepted, so it can be concluded that studentâs understanding of mathematical concept by applying true or false or false strategy with quiz is better than by using conventional strategy at eightth grade of SMPN 1 Koto Balingka.Â